Peningkatan Berpikir Kritis Siswa Kelas IXB SMP melalui PBL Berbantuan QuizWhizzer - Benyamin Pagi; Ansel Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
Many students still struggle to express their opinions critically, which results in low participation in learning activities. Therefore, an ideal learning environment is needed through the transformation of instructional models. This study aims to explore the implementation of the Problem-Based Learning (PBL) model combined with interactive technology-based media, namely QuizWhizzer, in Catholic Religious Education. The research focuses on improving the critical thinking skills of Grade IX students at SMP Panca Setya 2 Sintang during the second semester of the 2024/2025 academic year. The primary objective of this study is to determine whether the use of the PBL model assisted by QuizWhizzer can enhance students' critical thinking abilities. This classroom action research was conducted in two cycles using observation and test instruments. The results of the second cycle showed that the integration of PBL and QuizWhizzer significantly encouraged student engagement, strengthened analytical thinking processes, and created an enjoyable and stimulating learning atmosphere. The average cognitive evaluation score increased from 76 in the first cycle to 83 in the second cycle. Therefore, innovation in teaching strategies and media is essential for improving the quality of education, especially in addressing the challenges of learning in the digital era.